Unilesional folliculotropic mycosis fungoides: a unique variant of cutaneous lymphoma. (18th November 2014) - Amitay‐Laish, I.; Feinmesser, M.; Ben‐Amitai, D.; Fenig, E.; Sorin, D.; Hodak, E.
Abstract: Background: Unilesional folliculotropic mycosis fungoides (UFMF) has been rarely reported. Objective: The aim of this study was to describe our experience with UFMF. Methods: Data were collected on all patients with clinicopathological UFMF who attended the Department of Dermatology of a tertiary university‐affiliated medical centre in 1996–2013 and were followed prospectively. Results: The sample included seven patients (five male, two female) of mean age 38 years at diagnosis; two were aged <18 years. The lesion presented as a solitary patch/plaque with follicular accentuation in five patients, an infiltrated plaque devoid of hair in one and with follicular nodules in one. Four patients had alopecia, and one, secondary anetoderma. The lesion was located on a limb in four patients, the trunk in two, and the face in one. In all cases, the atypical folliculotropic lymphocytes expressed mainly surface CD4 + . Monoclonality was detected in three of the six patients analysed. Treatment consisted of localized electron beam in five patients, all of whom had a complete response (CR), and excision in one patient. The remaining patient, a 9‐year‐old boy, was treated with topical psoralen and UVA with CR. The duration of follow‐up was 0.5‐10 years (mean 4). There were no recurrences in six patients and local recurrence in one. Conclusion: UFMF presents at a young age, usually with early disease clinical morphology. The treatment goal should be cure. Our experience indicates an excellent prognosis of early UFMF with no multifocal/internal spread.